2011
DOI: 10.1007/s11046-011-9507-6
|View full text |Cite
|
Sign up to set email alerts
|

Combined Therapy of Voriconazole and Anidulafungin in Murine Infections by Aspergillus flavus

Abstract: The efficacy of the combination of anidulafungin (AFG) at 1 mg/kg plus voriconazole (VRC) at 25 mg/kg was evaluated in a murine model of disseminated infection by Aspergillus flavus using three isolates previously tested in vitro. All the combinations showed indifferent in vitro interaction with the exception of one, which showed synergy. In general, the combined treatment prolonged the survival and reduced the fungal load in comparison with AFG alone, and only in a few cases, it improved the results of the VR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 32 publications
4
14
0
Order By: Relevance
“…Although the FIC index range of 0.5 to 4 was proposed to define additive/indifferent interactions (53), this range is very broad to detect significant pharmacodynamic interactions, and combinations with FIC indices of Ͻ1 and Ͼ1.25 were found in vivo to be synergistic and antagonistic, respectively (48,54,55). These cutoffs may also be reliable for voriconazole-echinocandin combinations, since it was previously found that the voriconazole-anidulafungin combination prolonged survival compared to monotherapy in vitro when the FIC index was 0.5 to 1 (16). By using a cutoff value of 1, most of the in vitro combinations were synergistic rather than additive, as found in the present study (15,56).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Although the FIC index range of 0.5 to 4 was proposed to define additive/indifferent interactions (53), this range is very broad to detect significant pharmacodynamic interactions, and combinations with FIC indices of Ͻ1 and Ͼ1.25 were found in vivo to be synergistic and antagonistic, respectively (48,54,55). These cutoffs may also be reliable for voriconazole-echinocandin combinations, since it was previously found that the voriconazole-anidulafungin combination prolonged survival compared to monotherapy in vitro when the FIC index was 0.5 to 1 (16). By using a cutoff value of 1, most of the in vitro combinations were synergistic rather than additive, as found in the present study (15,56).…”
Section: Discussionsupporting
confidence: 62%
“…However, pharmacodynamic interactions in clinical trials may be obscured by confounding factors such as underlying disease, concomitant therapy, and toxicity and because combination regimens were compared with one of the two monotherapy regimens without taking into account the effect of the second drug. Most of the available information concerning the efficacy of antifungal combinational therapy comes from preclinical studies, with in vitro studies demonstrating mostly synergistic-to-additive/indifferent interactions (10)(11)(12)(13)(14)(15) and in vivo studies showing mostly no significant improvement compared to monotherapy (16)(17)(18)(19)(20)(21)(22)(23)(24)(25).…”
mentioning
confidence: 99%
“…In the present study, only one dose of voriconazole was evaluated because the use (4) 9.3 (6-30) 7.3 (6)(7)(8)(9)(10)(11)(12)(13)(14) of an additional dose for the same strains would have required more than 40 groups of animals. The dose tested demonstrated efficacy as seen in previous similar studies (9,27), and using this dose, the serum levels of that drug were always greater than the MICs for the strains tested. A possible limitation of the present study is the use of a systemic infection model, which is not the most common clinical presentation of A. fumigatus infection.…”
Section: Discussionsupporting
confidence: 67%
“…once daily (28), and AFG at 10 mg/kg i.p. once daily (29). Drug level determinations were not performed.…”
Section: Methodsmentioning
confidence: 99%